Dietary γ-Aminobutyric Acid Promotes Growth and Immune System Performance and Improves Erythropoiesis and Angiogenesis in Gibel Carp (Carassius auratus gibelio) - Xinlan Bai; Lu Zhang; Hualiang Liang; Dongyu Huang; Mingchun Ren; Haifeng Mi (Animals)
This experiment aimed to investigate the effect of dietary supplementation of γ-aminobutyric acid (GABA) on the growth performance, immune response, and oxygen-transport-related factors of Gibel carp (Carassius auratus gibelio). An eight-week culturing experiment was designed with five experimental diets, with the actual GABA content being 368 mg/kg (G1, control group), 449 mg/kg (G2), 527 mg/kg (G3), 602 mg/kg (G4), and 675 mg/kg (G5). The results showed that the level of 527 mg/kg (G3) of GABA significantly increased the specific growth rate (SGR), weight gain rate (WGR), and final body weight (FBW) of Gibel carp, while the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol (TC), and glucose (GLU) were also increased significantly. In addition, 527 mg/kg (G3) and 602 mg/kg (G4) of GABA significantly increased the total antioxidant capacity (T-AOC). The mRNA expression of tnf-α, tgf-β, and il-10 was significantly increased at the level of 449 mg/kg (G2). In terms of oxygen-carrying capacity, the mRNA expression of epo, tf, tfr1, ho-1, and vegf was markedly increased at the level of 449 mg/kg (G2). In conclusion, dietary GABA supplementation can boost growth performance, enhance the immune system, and increase oxygen-carrying capacity in Gibel carp.